Injection Characteristics of Gasohol using a Common Rail Injection System - Munsin, Ronnachart; Nattsirapong, Ichkan; Nuntapap, Nawee; Narkpakdee, Jerawich; Nilapai, Ob; Srichai, Prathan; Chaiyat, Nattaporn (Food Agricultural Sciences and Technology, 2019)
The worldwide emission regulations for compression ignition (CI) engines have become more stringent driven by global warming issues and public health concerns. A promising solution to decrease greenhouse gas and emissions from CI engines is gasohol considered as a fuel-replacing diesel. The objective of this study is to study effect of gasohol on fuel injection characteristics of a common rail injection system used in CI engines. Gasohol E85, containing 85% ethanol and 15% gasoline, is tested and conventional diesel is a reference fuel. An injection measurement device based on Zeuch method was used for investigating the injection characteristics including injected amount and discharge coeffi cient. Gasohol were injected with both single and double injection strategies at a constant injection pressure of 450 bar into a back-pressure of 40 bar. The fi ndings of this study clearly show that injection characteristics of gasohol were signifi cantly differed from those of diesel, due to physical properties changed. At the same injection conditions, injected fuel rate are different.